IMPLEMENTASI METODE IQRO' DALAM MENINGKATKAN KEFASIHAN MEMBACA AL-QUR’AN PADA SISWA SD NEGERI 12 SAMPOINIET - Muniteria (Journal of Community Devation, 2025)
There are various problems faced by fourth grade students at SD Negeri 01 Kajen, many students cannot read connected reading, long and short reading and there are students who are difficult to manage, sometimes these students even don't want to read iqro' or the Al-Qur'an for various reasons such as The iqro' is lost so the student is not fluent when reading and does not pass to read to the next page. The Iqro' method is a medium for learning the Al-Qur'an from the introduction of hijaiyah letters which is adapted based on volumes one to six. It is hoped that the use of the iqro' method will be able to provide good changes for students at SD Negeri 01 Kajen. The problems that researchers put forward in this research include: (1) How is the implementation of the Iqro' method in increasing fluency in reading the Al-Qur'an in class IV students at SD Negeri 12 Sampoiniet? (2) What are the supporting and inhibiting factors for implementing the Iqro' method in increasing fluency in reading the Al-Qur'an in class IV students at SD Negeri 12 Sampoiniet? Meanwhile, the objectives of this research are (1) To describe the implementation of the Iqro' method in improving fluency in reading the Al-Qur'an in class IV students at SD Negeri 12 Sampoiniet. (2) To find out what are the supporting and inhibiting factors for implementing the Iqro' method in improving fluency in reading the Al-Qur'an in class IV students at SD Negeri 12 Sampoiniet. (2) To find out what are the supporting and inhibiting factors for implementing the Iqro' method in increasing fluency in reading the Al-Qur'an in Class IV Students at SD Negeri 12 Sampoiniet. This research includes field research and uses a qualitative approach. Data collection techniques use observation, interviews and documentation methods. Data sources in research are primary data sources and secondary data. Data analysis techniques use data reduction, data presentation, and drawing conclusions. The results of this research are that the implementation of the iqro' method in improving fluency in reading the Al-Qur'an in class IV students at SD Negeri 12 Sampoiniet includes three stages, namely planning, implementation and evaluation. Meanwhile, internal supporting factors include students' self-motivation and high intelligence factors, while external supporting factors include a good social environment, teacher or ustadz education patterns, and parental supervision and support. Inhibiting factors include relatively short time, lack of teacher educators, and noisy classroom conditions.